A Comparion of the Performances of Type A Mutual Funds Before and After 2008 Global Economic Crisis in Turkey - Eşref Savaş Başçi; Fatih Memiş (Journal of Social and Administrative Sciences, 2014)
Looking from a historical perspective, financial activities contain many crises in itself. This situation seems to be a feature inherent in the existing economic system and as long as this system continues, it becomes inevitable being faced with the crisis. Especially in recent years, with the increasing globalization, the risk of being faced with a crisis has also increased. In the financial markets, savers who wish to evaluate the accumulation by investing in different investment tools may encounter some difficulties in the face of a variety of financial products and in times of crisis. Mutual funds consist of investment tools which have increasing importance in the capital market and give professional management services to savers in accordance with certain principles. Especially in recent years, mutual funds market is rapidly evolving in Turkey, as well as in the international market. Due to these developments, consideration of growing number of investors and growing portfolios of mutual funds emerges as a necessity. The purpose of this study is to compare the performances of type A mutual funds in Turkey for the period before and after the 2008 crisis. The pre-crisis period have been determined as 2005-2007 and the post-crisis period as 2009-2011. Within the scope of application, there are 74 mutual funds of type A, which continuously operated between January 2005 - December 2007 and January 2009 - December 2011, not joined with another fund, not taken over by another fund, not being in liquidation and having complete data. These mutual funds were analyzed by using performance measurement methods.
Keywords: L25; G2; G17; H12; 330; 2008 Economic Crisis in Turkey; Mutual Funds; Performance Measurement Methods